Advertisements
Advertisements
प्रश्न
If \[x = 7 + 4\sqrt{3}\] and xy =1, then \[\frac{1}{x^2} + \frac{1}{y^2} =\]
पर्याय
64
134
194
1/49
उत्तर
Given that `x=7+4sqrt3`, `xy = 1`
Hence y is given as
`y=1/x`
`1/x = 1/(7+4sqrt3)`
We need to find `1/x^2+ 1/y^2`
We know that rationalization factor for `7+4sqrt3` is `7-4sqrt3`. We will multiply numerator and denominator of the given expression `1/(7+4sqrt3)`by,`7-4sqrt3` to get
`1/x = 1/(7+4sqrt3) xx (7-4sqrt3)/(7-4sqrt3)`
`= (7-4sqrt3)/((7)^2 (4sqrt3)^2) `
` = (7-4sqrt3)/(49 - 48)`
` = 7-4sqrt3`
Since `xy=1`so we have
`x=1/y`
Therefore,
`1/x^2 + 1/y^2 = ( 7 - sqrt3)^2 + (7+4sqrt3)^2`
` = 7^2 + (4sqrt3)^2 - 2 xx 7 xx 4sqrt3 + 7 ^2 +(4 sqrt3)^2 + 2 xx 7 xx 4sqrt3`
`= 49 + 48 - 14 sqrt3 + 49 +48 +14sqrt3`
`= 194`
APPEARS IN
संबंधित प्रश्न
Simplify the following:
`(3^nxx9^(n+1))/(3^(n-1)xx9^(n-1))`
Solve the following equation for x:
`2^(5x+3)=8^(x+3)`
Solve the following equations for x:
`2^(2x)-2^(x+3)+2^4=0`
If `a=xy^(p-1), b=xy^(q-1)` and `c=xy^(r-1),` prove that `a^(q-r)b^(r-p)c^(p-q)=1`
Prove that:
`sqrt(3xx5^-3)divroot3(3^-1)sqrt5xxroot6(3xx5^6)=3/5`
Show that:
`(x^(a^2+b^2)/x^(ab))^(a+b)(x^(b^2+c^2)/x^(bc))^(b+c)(x^(c^2+a^2)/x^(ac))^(a+c)=x^(2(a^3+b^3+c^3))`
`(2/3)^x (3/2)^(2x)=81/16 `then x =
The value of \[\left\{ 8^{- 4/3} \div 2^{- 2} \right\}^{1/2}\] is
If \[\frac{x}{x^{1 . 5}} = 8 x^{- 1}\] and x > 0, then x =
If \[\sqrt{13 - a\sqrt{10}} = \sqrt{8} + \sqrt{5}, \text { then a } =\]